Playing defence: the impact of trust on the coping mechanisms of street-level bureaucrats. Issue 2 (1st February 2022) - Davidovitz, Maayan; Cohen, Nissim
ABSTRACT: According to public management literature, trust has a positive influence on behaviour. Why, then, do street-level bureaucrats (SLBs) appear to favour clients whom they do not trust, and give less attention to those they do trust? Do organizational conditions play a role in this dynamic? We investigate these issues as they affect Israeli social services providers. Our study improves our understanding of trust as a factor in public service delivery. When SLBs operate in an unsupportive environment, they prioritize clients whom they distrust, bending or breaking rules for them, yet ration services to clients whom they trust.